Comparative genomics of the restriction-modification systems in Helicobacter pylori - Lin, Lee-Fong (The National Academy of Sciences, 2001)
Helicobacter pylori is a Gram-negative bacterial pathogen with a small genome of 1.64–1.67 Mb. More than 20 putative DNA restriction-modification (R-M) systems, comprising more than 4% of the total genome, have been identified in the two completely sequenced H. pylori strains, 26695 and J99, based on sequence similarities. In this study, we have investigated the biochemical activities of 14 Type II R-M systems in H. pylori 26695. Less than 30% of the Type II R-M systems in 26695 are fully functional, similar to the results obtained from strain J99. Although nearly 90% of the R-M genes are shared by the two H. pylori strains, different sets of these R-M genes are functionally active in each strain. Interestingly, all strain-specific R-M genes are active, whereas most shared genes are inactive. This agrees with the notion that strain-specific genes have been acquired more recently through horizontal transfer from other bacteria and selected for function. Thus, they are less likely to be impaired by random mutations. Our results also show that H. pylori has extremely diversified R-M systems in different strains, and that the diversity may be maintained by constantly acquiring new R-M systems and by inactivating and deleting the old ones.